Innovative and Sustainable Management Practices Using Qatari Mycorrhizae Fertilizers for Enhanced Production of Green beans - Naema A. Yahya (23752905) (2025)
Recent attention has been directed towards developing innovative and sustainable agricultural practices using native mycorrhizal fertilizers to enhance vegetable crop production in arid environments. Qatar's unique arid climate presents both challenges and opportunities for implementing bio-based fertilization strategies. This research aims to investigate the effectiveness of Qatari native arbuscular mycorrhizal fungi (AMF) consortia as innovative biofertilizers for sustainable vegetable production under varying irrigation conditions. Mycorrhizal consortia comprising species from Glomus, Acaulospora, and Claroideoglomus genera were isolated from nine representative Qatari locations and evaluated for their potential as sustainable fertilizers. A comprehensive greenhouse experiment was conducted using common bean (Phaseolus vulgaris L.) as a model vegetable crop under two irrigation regimes (50% and 100% field capacity) with three mycorrhizal fertilizer treatments: uninoculated control, 50g AMF consortium, and 100g AMF consortium applications. The investigation focused on growth enhancement, nutrient acquisition efficiency, root colonization dynamics, productivity parameters, and stress tolerance mechanisms. Results demonstrated that Qatari native AMF consortia significantly improved plant performance across all measured parameters compared to conventional controls. The highest mycorrhizal fertilizer concentration consistently produced superior results, with enhanced shoot and root biomass, improved nutrient uptake (N, P, K), increased pod yield, and elevated stress tolerance indicators including proline accumulation and soil enzyme activities. Under water-deficit conditions, mycorrhizal-treated plants exhibited remarkable resilience, demonstrating the effectiveness of these native biofertilizers in mitigating abiotic stress. Even under optimal irrigation, inoculated plants showed consistent improvements over controls, indicating broad applicability of these sustainable fertilization practices. This study provides the first comprehensive evaluation of Qatari native mycorrhizal fungi as innovative biofertilizers for vegetable production, offering promising prospects for developing sustainable agricultural systems and enhancing food security in arid regions through environmentally friendly fertilization approaches. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx